Paradigma Dan Pemikiran Kepemimpinan Kepala Sekolah/Madrasah Dalam Meningkatkan Mutu Pembelajaran PAI - Islami, Hanifan; Januar (Rayah Al-Islam, 2025)
The leadership of the principal or madrasah has an important role in improving the quality of education, especially in the field of Islamic Religious Education (PAI). A principal is not only tasked with managing administration effectively, but the principal also motivates and directs all parties involved in education to achieve the targets that have been set. This article aims to discuss various paradigms and thoughts on the leadership of the principal in the context of PAI, as well as to explore the competence, type of leadership, and responsibilities of the principal in improving the quality of PAI. In addition, this article also identifies various problems that are often faced by principals and provides solutions to overcome these challenges. The research method used in this study is descriptive qualitative with secondary data research data sources, data collection techniques are carried out through documentation studies and analyzed using content analysis techniques. Based on this study, it was found that an effective principal must have competencies in managerial, pedagogical, leadership, and social, and can apply various types of leadership to support improving the quality of PAI. Solutions to overcome various problems faced by principals, such as the lack of PAI teacher skills and difficulties in implementing the curriculum, can be found through training for teachers and adjusting the curriculum to be more flexible.